Lexical Creativity in Online Music Reviews - Karolina Ryker (Półrocznik Językoznawczy Tertium)
The language of the 21st century encompasses a wide array of texts, many of which can be found on the Internet. While the language of Internet blogs, posts and memes has received considerable attention from scholars, the language of online music reviews remains one of the most underresearched Internet genres. One of the music reviewing websites offering lexically creative content is Pitchfork. Authors of the reviews are prolific with regard to the creation of hyphenated neologistic compounds such as all-proceeds-to-charity wine, the last-real-gangsta-standing attitude and smartphone-sucking lives. The aim of this study is to analyse hyphenated compound occasionalisms and neologisms in Pitchfork music reviews in terms of their meaning, structure and function. The analysis features compounds obtained from the corpus of music reviews created for the purpose of the study. Quantitative analysis involves all compounds in the reviews, while qualitative analysis is employed for neologistic compounds. The findings indicate that two-element compounds are the most common in the corpus as far as compound structure is concerned. In terms of the syntactic criterion, compound adjectives are the most frequently used, followed by compound nouns, with few instances of compound verbs and adverbs. Neologistic compounds are employed for the purposes of ludic wordplay as well as achieving humour and irony. The most salient features of neologistic compounds are high context-dependence, unpredictability and allusions to pop-culture.